2018
DOI: 10.3389/fmolb.2018.00043
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of AQP1 IS Modified in Lung of Patients With Idiopathic Pulmonary Fibrosis: Addressing a Possible New Target

Abstract: Activation of the epithelial-mesenchymal transition process (EMT) by which alveolar cells in human lung tissue undergo differentiation giving rise to a mesenchymal phenotype (fibroblast/miofibroblasts) has been well recognized as a key element in the origin of idiopathic pulmonary fibrosis (IPF). Here we analyzed expression of AQP1 in lung biopsies of patients diagnosed with IPF, and compared it to biopsies derived from patients with diverse lung pneumonies, such as hypersensitivity pneumonitis, sarcoidosis or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[58]. Screening of human IPF lung biopsies revealed clearly elevated AQP1 levels in alveolar epithelia [59]. In vitro analysis in this study comparing IPF patient-derived versus healthy lung-derived fibroblasts showed AQP1 induction in response to TGF-β treatment in the former, implying AQP1 role in the pro-fibrotic TGF-β action and IPF etiology/pathophysiology.…”
Section: Pulmonary Infections Stress and Toxicity-lung Infections (Bacterial Viralmentioning
confidence: 57%
“…[58]. Screening of human IPF lung biopsies revealed clearly elevated AQP1 levels in alveolar epithelia [59]. In vitro analysis in this study comparing IPF patient-derived versus healthy lung-derived fibroblasts showed AQP1 induction in response to TGF-β treatment in the former, implying AQP1 role in the pro-fibrotic TGF-β action and IPF etiology/pathophysiology.…”
Section: Pulmonary Infections Stress and Toxicity-lung Infections (Bacterial Viralmentioning
confidence: 57%
“…It should be noted that the previous studies exploring the effect of deleting AQP1 on hypoxia-induced PH did not do so in a cell-type-specific manner, and various cells within the lung have been shown to express AQP1. For example, AQP1 expression has been reported in human and rat PASMCs (Leggett et al, 2012;Schuoler et al, 2017), macrophages (Rabolli et al, 2014;Tyteca et al, 2015), human activated T and B cells (Moon et al, 2004) and human and mouse type II pneumocytes (Effros et al, 1997;Galan-Cobo et al, 2018); however, staining for AQP1 was not observed in rat alveolar epithelium (Nielsen et al, 1997) or mouse type I cells (Effros et al, 1997). Thus, while the reduced development of hypoxiainduced PH in the previous studies could have resulted from the loss of AQP1 in PASMCs or MVECs, a role for AQP1 in other cell types cannot be ruled out at this point.…”
Section: Discussionmentioning
confidence: 99%
“…However, the specific pathogenesis has not been completely clear. The study of mouse model [ 3 , 4 ] and patients with idiopathic pulmonary fibrosis (IPF) [ 5 ] showed that there was a close relationship between the epithelial–mesenchymal transition (EMT) and the process of pulmonary fibrosis. EMT is a biological process in which epithelial cells transform into cells with a mesenchymal phenotype, which is characterized by decreased expression of epithelial markers and increased expression of mesenchymal markers.…”
Section: Introductionmentioning
confidence: 99%